Simultaneous determination of the lattice thermal conductivity and grain/grain thermal resistance in polycrystalline diamond. (15th October 2017) - Anaya, J.; Bai, T.; Wang, Y.; Li, C.; Goorsky, M.; Bougher, T.L.; Yates, L.; Cheng, Z.; Graham, S.; Hobart, K.D.; Feygelson, T.I.; Tadjer, M.J.; et al.
Abstract: The in-plane and cross-plane thermal conductivity of polycrystalline diamond near its nucleation region have been measured by Raman thermography assisted by TiO2 nanoparticles and by picosecond time-domain thermoreflectance (TDTR). This information has been combined with a finite element thermal model making use of the real grain structure, including information on the grain orientation, of the film extracted by transmission electron microscopy (TEM). This methodology allows to simultaneously determine the thermal resistance between grains and the lattice thermal conductivity of the sample without any adjustable parameter. The results show that the lattice thermal conductivity of the near nucleation diamond is 5–8 times smaller than the one observed in IIa single-crystalline diamond; the thermal resistance between grains is at least one order of magnitude higher than values predicted by molecular dynamic simulations. Finally, we show how the anisotropy in thermal conductivity observed in polycrystalline diamond naturally emerges from its grain structure and the thermal resistance at grain boundaries. Graphical abstract: Image 1